Data fraud in clinical trials - George, Stephen (Henry Stewart Talks, 2016)
Definitions (fabrication, falsification, plagiarism), Prevalence of data fraud, Examples (Modern high-profile examples of research misconduct), Motivations: why did they do it?, Statistical detection